Token versus Team Work: Women in the Local Bodies of Nepal 2017 - Mahato, Sanjaya (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2023)
Taking the local elections data 1992, 1997 and 2017, and reviewing the development of institutions, the paper argues that the institutional shift has numerically boosted women from token to titled group in the local bodies of Nepal. It has provided a space to boost political leadership among women which does not necessarily lead to team work. Both formal and informal factors significantly hider women to make a team work. Party framework and anti-defection laws make elected women extremely loyal and accountable to the male dominated party leadership and limit their full participation. Similarly, mindset of the male political leaders and masculine social settings significantly prevents elected women to form a team work, and facilitates for full and meaningful participation in the local bodies. However, there are many hopes and aspirations that increase women as a titled and potential group helping them to push for women friendly policies based on how they negotiate with their male counterparts.